2020
DOI: 10.1111/desc.13041
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the developing language network in 4‐year‐old children predicts future reading ability

Abstract: Understanding how pre‐literate children's language abilities and neural function relate to future reading ability is important for identifying children who may be at‐risk for reading problems. Pre‐literate children are already proficient users of spoken language and their developing brain networks for language become highly overlapping with brain networks that emerge during literacy acquisition. In the present longitudinal study, we examined language abilities, and neural activation and connectivity within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 102 publications
(151 reference statements)
3
32
1
Order By: Relevance
“…The fact that the Brain-and-Behavior model was found to be the best fitting model suggests that in line with previous investigations (e.g., Hoeft et al, 2007Hoeft et al, , 2011Maurer et al, 2009;Bach et al, 2013;Myers et al, 2014;Borchers et al, 2019;Jasińska et al, 2020), both neural and behavioral measures explain unique variance in reading growth. However, it should be noted that when evaluating the Brain and Behavior models separately, substantially more evidence was found in favor of the Behavior model as compared to the Brain model.…”
Section: H2: Neural Specialization Will Be a Stronger Predictor Than Behavioral Measuressupporting
confidence: 86%
See 2 more Smart Citations
“…The fact that the Brain-and-Behavior model was found to be the best fitting model suggests that in line with previous investigations (e.g., Hoeft et al, 2007Hoeft et al, , 2011Maurer et al, 2009;Bach et al, 2013;Myers et al, 2014;Borchers et al, 2019;Jasińska et al, 2020), both neural and behavioral measures explain unique variance in reading growth. However, it should be noted that when evaluating the Brain and Behavior models separately, substantially more evidence was found in favor of the Behavior model as compared to the Brain model.…”
Section: H2: Neural Specialization Will Be a Stronger Predictor Than Behavioral Measuressupporting
confidence: 86%
“…The limited existing research in which both behavioral and brain-based measures have been used to predict growth in early reading skills has consistently demonstrated that neural measures explain unique variance over that of behavioral measures (e.g., Hoeft et al, 2007 , 2011 ; Maurer et al, 2009 ; Bach et al, 2013 ; Myers et al, 2014 ; Borchers et al, 2019 ; Jasińska et al, 2020 ). In fact, in at least one study, neural measures were found to be predictive of reading growth even when behavioral measures were not (Hoeft et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, questions remain about how the contributions of connectivity and variability to TD/RD differences change over age and experience. Much like in the case of mean activation differences, it is crucial that future research examine whether these differences are present already from a young age (as suggested, for example, by studies showing prospective correlations of connectivity before literacy onset and later reading skills, Jasińska et al, 2020 ), or whether the profiles we see in adults and adolescents is the result of a differential growth in these metrics over age and/or exposure to print in TD and RD populations ( Morken et al, 2017 ). A second open question has to do with the multi-dimensional nature of RD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in microstructure have been demonstrated following intensive reading interventions (Keller and Just, 2009; Huber et al, 2018). Importantly, longitudinal studies indicate activation and functional connectivity in reading related regions are related to language skill gains (Xiao et al, 2016) and later reading outcomes (Jasińska et al, 2020) during early childhood. In general, children with higher reading proficiency show faster development of reading-related brain regions than children with poor reading skills (Yeatman et al, 2012b; Wang et al, 2017; Reynolds et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%